Selective Exposure Patterns to the Iraqi Daily Newspapers and Its Motives for Iraqi University Students (College of Mass Communication - University of Baghdad as a Model) - Abood al-Ammar, Nada (ALBAHITH ALALAMI, 2013)
This study examines patterns of exposure of Iraqi university students to selective daily Iraqi newspapers and the motives of this exposure, as well as its associated factors that affect the average exposure. It tries to answer several questions, including those related to the levels of exposure of Iraqi university students to daily Iraqi newspapers and classification of patterns of selective exposure to daily Iraqi newspapers and the most prominent Iraqi daily newspapers that are selectively exposed by Iraqi university students. It also examines the motives of this selective exposure and factors that increase the degree of exposure to the daily Iraqi newspapers, and the most prominent stages in which Iraqi university students find their action of exposure to these newspapers. This study consists of three axes. The first concerns the systematic framework in terms of defining the research problem, objectives and methodology used. The second, the study used the curriculum survey and questionnaire tool to obtain the required data. Whereas, the third one included theoretical input in terms of defining the concept of selective exposure and the concept of motivation, according to interpretations by the sciences of sociology and psychology, as well as for determining the types of exposure motives and patterns. The study found a number of findings and conclusions that emerged from the field study by analyzing the questionnaire data and process it statistically using the percentage.